1999
DOI: 10.1021/la990151j
|View full text |Cite
|
Sign up to set email alerts
|

Orientational Arrangement of Long-Chain Fluorescein Molecules within the Monolayer at the Air/Water Interface Studied by the SHG Technique

Abstract: Orientational arrangement of long-chain Fluorescein O322 molecules within the monolayer at the air/water interface induced by the compression process was studied by surface second harmonic generation. Compression does not change the average tilt angle of the chromophore in any significant way, but it induces the alignment of the chromophore along a preferred direction perpendicular to the compression direction, originating the in-plane optical anisotropy. A model has been proposed on the orientational ordering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
0
15
2
Order By: Relevance
“…Despite their extensive applications in cell and molecular biology as well as in chemical research for a long time, limited systematic studies have been conducted to investigate the Langmuir monolayer properties of these fluorescent lipid molecules alone. Tsukanova et al 9 recently published a Langmuir monolayer study of (5-octadecanoylamino)fluorescein (Molecular Probe catalog number O322, ODFL). 9 Despite the small molecular size of ODFL with one alkyl chain attached to fluorescein, it is surprising for us to see that the reported surface pressure-area isotherm measurements gave the limiting molecular area of approximately 110 Å 2 molecule -1 for its monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their extensive applications in cell and molecular biology as well as in chemical research for a long time, limited systematic studies have been conducted to investigate the Langmuir monolayer properties of these fluorescent lipid molecules alone. Tsukanova et al 9 recently published a Langmuir monolayer study of (5-octadecanoylamino)fluorescein (Molecular Probe catalog number O322, ODFL). 9 Despite the small molecular size of ODFL with one alkyl chain attached to fluorescein, it is surprising for us to see that the reported surface pressure-area isotherm measurements gave the limiting molecular area of approximately 110 Å 2 molecule -1 for its monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…The same orientation is expected for those complexes formed with adipate, glutarate and succinate; however, with malonate another geometry, one with both fluorophores in almost orthogonal planes (Figure 6), seems to be more favourable 19. By taking into acount that the S 0 → S 1 transition moments of both fluorescein20 and rhodamine B21 derivatives are parallel to the long axis of the xanthene ring system, it is expected that these transition moments are in orthogonal planes in the complex with malonate.…”
Section: Resultsmentioning
confidence: 99%
“…70° at a low surface density, and it increases with the surface density increase. It has been found that the tilt angle of fluorescein O322, which has a COOH group, an OH group, and a long chain of octadecanes, was about 54° to the normal of the surface at 2.3−0.83 nm 2 /molecule by the second harmonic generation technique . A molecule with a hydrophilic group and a large conjugated hydrophobic group could be expected to stay on a slant orientation while the hydrophilic group is in the water.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, the monolayer at the liquid−air interface has been studied with the Langmuir technique by measuring the surface pressure upon compression of the surface monolayer. Recently, new laser spectroscopic methods such as second harmonic and sum-frequency generations have proven to be an invaluable tool in investigating the orientation of molecules at the air−water interface. Laser two-photon ionization is an important surface technique as well . The photoabsorbing molecules in solution, , on the solid surface, and on the water surface , can be efficiently photoionized in a two-photon process by laser irradiation.…”
Section: Introductionmentioning
confidence: 99%